Mechanisms of obesogens and their impact on adipose tissue, hormones, and inflammation (Journal of Medical Science, 2024)
The complex interactions of genetic, environmental, and behavioral factors that contribute to obesity, a pervasive global health issue, continue to be a severe concern for people all over the world. This manuscript examines the field of obesogen research, seeking to understand the mechanisms by which certain environmental chemicals contribute to the development of obesity. We explore the obesogenic effects by focusing on pathways such as inflammation, hormone interference, and the activation of peroxisome proliferator-activated receptors (PPARs). The text focuses on the significance of PPAR isoforms, especially PPARγ, and how they play a role in adipose tissue growth. We examine how obesogens such as tributyltin (TBT) and bisphenol A (BPA) influence these receptors. Additionally, we examined the impact of obesogens on hormonal regulation, including disruptions to leptin and adiponectin, and investigated the intricate relationship between chronic inflammation and obesity. In the methodology of our study, we utilized a systematic search to identify peer-reviewed articles of relevance. This search spanned various model systems, including in vitro, in vivo, and epidemiological studies, providing insights into the distinct advantages and limitations associated with each. Epigenetic modifications and the influence of obesogens on the development of adipose tissue, metabolism, and appetite control further enrich our understanding of this complex field. Finally, we assess the role of endocrine disruptors in amplifying the risk of obesity, emphasizing the heightened susceptibility during crucial developmental periods. This comprehensive review aims to contribute to the ongoing discourse surrounding obesogens, paving the way for targeted interventions and a more profound comprehension of the global obesity epidemic.